THE INFLUENCE OF BRAND IMAGE AND COMPLAINT HANDLING ON REVISIT INTENTION WITH PATIENT EXPERIENCE AS AN INTERVENING VARIABLE - Saputro, Dimas Kuncoro (Journal of Hospital Management, 2023)
This research is based on a decrease in the number of patient visits in 2022 when compared to 2021. The purpose of this study was to empirically reveal the effect of brand image and complaint handling on intention to return visits with patient experience as an intervening variable. This research is included in the quantitative research with a causality approach, the population used is patients who have visited more than once, the sample calculation uses the indicator formula x 5, so that a sample of 240 respondents is obtained using accidental sampling technique. The analytical method used is the three-box method and SEM analysis. The results of the analysis concluded that brand image and complaint handling had an effect on repeat visit intentions with trust as an intervening variable, brand image and complaint handling had an effect on experience and intention to revisit, and patient experience had an effect on repeat visits intentions, as well as providing positive intervention on brand image relations. and handling of complaints about intention to return visits. Several things that must be done to maintain the patient's intention to return visits are to make improvements to the promotion system using methods to build patient trust and loyalty, improvements to the system for conveying patient complaints, improvements to the patient centered care system and improvements to the promotion system uses the endorsement method.Keywords: Brand image, complaint handling, patient experience, repeat visit intention